The impact of shading levels on users' thermal comfort in public leisure spaces - Faustini, Fabiana Benevenuto [UNESP]; Maia, Marina Lisboa [UNESP]; Rioli, Thyssie Ortolani [UNESP]; de Faria, João Roberto Gomes [UNESP]; de Castro Fontes, Maria Solange Gurgel [UNESP] (My University, 2017)
The knowledge about microclimate and its influence on people's thermal comfort becomes critical to the planning process of all types of environment. In leisure facility design, guaranteeing the user's thermal comfort has become increasingly essential, since it affects the activities, usage characteristics and the time people spent in these spaces. Recent researches on thermal comfort aim at creating guidelines for attractive outdoor environments that contribute to improve urban quality of life and consider environmental factors (air temperature, wind speed and relative humidity), which affect the users' thermal perception and satisfaction. In this context, this pilot project of a larger project investigated how the different levels of shading affect users' thermal comfort in outdoor leisure spaces. It was conducted in Bauru Municipal Zoo Park, São Paulo State, Brazil, through the analysis of microclimatic research, questionnaires, and field observations in cold weather conditions for three days. These surveys allowed to identify the actual sensation votes (ASV) calculated through the PET index (Physiological Equivalent Temperature), in two subspaces with the same attractiveness and different levels of shading. The analysis of the results highlighted: 1.Great number of comfortable users´ in the area with greater shading during times of greater solar heating; 2. Users' short exposure in the area of high incidence of direct solar radiation; and 3. Range of thermal neutrality in the PET index varied in relation to the two subspaces. The results show the close relationship between levels of shading, thermal comfort and exposure time in the outdoor space.
Keywords: Levels of shading; Outdoor thermal comfort; PET index; Time exposure; Urban parks